Seismotectonic analysis of the 2021 Damasi-Tyrnavos (Thessaly, Central Greece) earthquake sequence and implications on the stress field rotations. (March 2022) - Kassaras, Ioannis; Kapetanidis, Vasilis; Ganas, Athanassios; Karakonstantis, Andreas; Papadimitriou, Panayotis; Kaviris, George; Kouskouna, Vasiliki; Voulgaris, Nicholas
Abstract: In early March 2021, three shallow earthquakes, two mainshocks with M6.3 and M6.0 and one major aftershock with M5.6 impacted both the mountainous Damasi-Tyrnavos region (northern Thessaly, Greece) and the adjacent Plio-Quaternary basin. Each major event was followed by rich aftershock activity recorded by local and regional seismographs and accelerographs. Herein, we present a comprehensive analysis of the seismic sequence, from its foreshock activity starting on 28 February, 2021 and for a period of two months using new high-resolution catalogues of relocated earthquakes and hundreds of focal mechanisms. The results indicate that the aftershocks form a zone that spans ~50 km NW-SE, while focal depths range between 5 and 15 km. More than 400 focal mechanisms, computed for events with M≥ 2.5, mainly exhibit normal faulting in a NW-SE direction, while WNW-ESE to E-W normal faulting is also evidenced, in particular after the occurrence of the last major event on 12 March. The stress-field was reconstructed on a local and broader scale by inverting focal mechanism data, revealing a rotation of the σ 3 axis trend from NNE-SSW, in the Damasi-broader region, to NW-SE northwards, to the region of Kozani-Grevena that hosted an M w = 6.6 shallow mainshock in 1995. Subcrustal seismicity, present beneath those areas, implies that large-scale tectonics and plate dynamics are likely involved in the deformation of the upper crust. Coulomb stress transfer after the 3 major events of the 2021 Damasi-Tyrnavos sequence reveals that stress-loaded areas include those where most aftershocks were triggered. The analysis provides implications to the seismic hazard of the activated area, as a major NW-SE active normal fault close to Larissa city became stress-loaded, constituting a possible candidate source for significant future earthquakes. Highlights: The seismotectonics of a cascade-type sequence of strong earthquakes was studied. The relocation of aftershocks revealed the geometry of the activated structures. The inversion of focal mechanisms revealed dominant pure extensional tectonics. The regional extensional stress was found to rotate from NE to NW towards the north. The observed stress pattern is likely explained by large-scale plate kinematics.